A tracking mechanism for medium and high concentration ratio parabolic trough solar collectors - Kalogirou, Soteris A.; Lloyd, Stephen J.; Ward, John Paul (My University, 1992)
This paper describes a tracking system for use with solar parabolic trough collectors. The position and "status" of the Sun are detected by three Light Dependent Resistors (LDRs), one of which detects whether the collector is focused, whilst a second resistor determines if there is cloud cover, and the third senses whether it is day or night. The resultant signals are fed to an electronic control system which operates a low speed 12 V d.c. motor which rotates the collector via a speed reduction gearbox. The system provides a tracking accuracy of 0.2 wich solar radiation of 100 W/m2 and 0.05 for solar radiation of 600 W/m2.
Keywords: Solar Parabolic